Peran Teknologi dalam Transformasi Sistem Akutansi dan Keuangan di Era Digital - Shafwan Aziz, Muhammad; Sriwardany, Sriwardany (Teewan Journal Solutions, 2025)
The digital era has brought significant changes to various sectors, including accounting and finance. Information technology, especially cloud-based software and applications, has changed the way companies manage and report their finances. This digital transformation not only speeds up the process of recording transactions, but also increases accuracy, efficiency, and transparency in financial reports. The use of technologies such as artificial intelligence (AI), blockchain, and data analytics allows accounting and finance professionals to identify patterns, manage risks, and make data-based decisions in a more timely and effective manner. However, challenges in implementing technology, such as the need for new skills for the workforce and data security issues, remain obstacles that must be overcome. This article aims to analyze the role of technology in the transformation of accounting and finance systems, as well as its impact on operational efficiency and the quality of decision-making in companies in the digital era.